Retributivisme Kultural: Eksplorasi Fenomena Pembunuhan Demi Kehormatan (Honor Killing) dalam Lensa Teori Kriminologi - Zul Khaidir Kadir (Jurnal Litigasi Amsir, 2024)
Honor killing is a culture-based killing carried out under the pretext of maintaining family honor, rooted in patriarchal norms and traditional values that prioritize family honor over individual rights and freedoms. This phenomenon is supported by a broader cultural and social system, although it is still legally considered a forbidden murder. This study uses qualitative methods to understand social phenomena and human behavior, with a conceptual approach and data collection through literature studies. The findings of the study suggest that honor killing can be seen as a form of cultural retribution, where killing is used as a symbolic response to the loss of family honor. Relevant criminological theories to explain honor killing include the theory of cultural transmission, the theory of cultural conflict, as well as several bio-criminological theories such as the theory of sexual selection, the theory of paternity certainty, and the theory of maladaptive killing.